Nephroprotective Activity of Aqueous Extract of Carica Papaya Seeds in Carbon Tetrachloride Induced Nephrotoxic Rats - Sultana, Mst Shahin; Saha, Rekha Rani; Islam, Sheikh Nazrul; Afrin, Tasnin; Afroz, Rumana; Lotus, Mahbuba Jahan (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: The kidney plays a dominant role in homeostasis by excreting the metabolic waste products and excess of necessary substances. It is a major excretory organ regulating water and electrolyte balance and conserving necessary products according to body needs. Nephrotoxicity is one of the most common kidney problems. A number of therapeutic agents can adversely affect the kidney resulting in acute renal failure, chronic interstitial nephritis and nephritic syndrome. Nephroprotective agents are the substances which possess protective activity against Nephrotoxicity. Early literatures have prescribed several herbal and medicinal plants, that are used as nephroprotective agents. Several herbal and medicinal plants are used as nephroprotective agents in experimental animals. Carica papaya was reported to have antioxidant and free radical scavenging activities. The present study was performed to determine the nephroprotective role of aqueous extract of Carica papaya seeds on carbon tetrachloride (CCl4) induced nephrotoxic rats. Methods: For the purpose of the study 28 healthy, male, wistar albino rats were taken and randomly divided into four groups (Group-A, Group-B, Group-C, and Group-D), each group formed of 7 rats. Group A received laboratory diet for 7 days. Group B received laboratory diet for 7 days. Group C and group D received aqueous extract of Carica papaya seeds (CPE) 250 mg/kg/day and 500 mg/kg/day respectively for 7 days. On 8th day a single intraperitoneal injection of 1.5 ml/kg of 20% CCl4 dissolved in olive oil was given to the rats of group B, group C and group D for induction of nephrotoxicity. All the animals were sacrificed on 11th day and their blood and kidney samples were collected. Serum creatinine, urea and uric acid were estimated and histopathology of kidney was done. Result: Result showed that the highest level of serum creatinine and urea were exhibited by the rats of Group-B and lowest level by the rats of Group-A. The levels of the same biochemical variables in Group-C and Group-D were in between the levels found in Group-A & Group-B (p = 0.004 and p = 0.001 respectively). The serum creatinine and urea levels remain normal and histopathological architecture was almost maintained in rats, treated with aqueous extract of Carica papaya seeds 500 mg/kg/day before nephrotoxicity induced in them by Carbon tetrachloride (CCl4) injection, although these biochemical values were elevated and histopathological structure was altered in rats, treated with Carbon tetrachloride (CCl4) injection and no CPE was given before (Group-B). The study also revealed that Carica papaya seeds 500 mg/kg/day was more protective than 250 mg/kg/day as was evidenced by lower serum urea level in the Group-D (31.73 ± 4.29 mg/dl) than that in Group-C (52.47 ± 5.38 mg/dl) (p < 0.001). Conclusion: The study concluded that Carica papaya seeds have nephroprotective activity against nephrotoxic effect of CCl4. Renal histological architecture was almost maintained by Carica papaya. Higher dose of Carica papaya provides better protection. Ibrahim Card Med J 2022; 12 (1): 9-17